The role of kindergarten teachers in developing language communication skills in children from their point of view - Alhejaili, Bayan Saleem (Journal of Educational and Psychological Sciences, 2022)
The present study aimed to identify the role of kindergarten teachers in developing children's language communication skills from their point of view. In order to achieve the objectives of the study, the descriptive approach was followed, whereby the study tool (the questionnaire) was applied to a sample of kindergarten teachers in Makkah Al- Mukarramah and the results were reached.The high role of kindergarten teachers in developing language communication skills in its dimensions (listening- speaking- readiness to read- readiness to write) from their point of view.As well as the roles of female teachers with a bachelor’s qualification, with educational preparation, qualification for an educational diploma and a master’s, are superior.The roles of kindergarten teachers with experience greater than 5 years and less than 10 in developing language communication skills compared to those with experience (5 years or less) and (10 years or more), and also the roles of preschool teachers in developing language communication skills compared to first- class teachers and kindergarten teachers second.
Keywords: Language communication skills; Kindergarten teachers